Gasdermin E in glioblastoma –pyroptosis resistance and tumor-promoting functions - Solel, Ege; Brudvik, Egil; Ystaas, Lars Andreas Rømo; Yabo, Yahaya; Rigg, Emma; Choudhury, Romi Roy; Saed, Halala Sdik; Heiland, Dieter Henrik; Bjerkvig, Rolf; Hossain, Jubayer; Miletic, Hrvoje (Cell Death Discovery, 2025)
Treatment of glioblastoma (GB), the most common and most aggressive malignant brain tumor, has made little progress over the past two decades. Despite extensive research on apoptosis and autophagy, necrotic cell death mechanisms like pyroptosis, which have the potential to stimulate anti-tumor immune responses, remain largely underexplored in GB. Here, we investigated whether Gasdermin E (GSDME)-mediated pyroptosis can be induced in GB by employing the drug raptinal, an inducer of cytochrome c release. Using human patient-derived and mouse GB cell lines, we showed that raptinal promotes GSMDE cleavage. However, although a strong pyroptotic response was observed in mouse cell lines, it was weak in human cell lines. This resistance was partially reversed by the calcium chelator BAPTA-AM, indicating that membrane repair mechanisms may counteract the pyroptotic response. Gsdme knockout (KO) in mouse GB cells unexpectedly prolonged the survival of immunocompetent mice, demonstrating a tumor-promoting role of GSDME independent of its pyroptotic function. Analysis of the immune microenvironment revealed that Gsdme KO promoted infiltration of T cells, which was confirmed by spatial transcriptomic analysis of GB patient samples. In addition, Gsdme/GSMDE KO reduced the invasive capacity of mouse/human GB cells. In conclusion, active membrane repair mechanisms may impair the pyroptotic efficacy in GB. GSDME has a tumor-promoting role in GB by suppressing T cell infiltration and increasing tumor cell invasion.
CRIS-Team Scopus Importer:2025-07-04